Desempenho hidrológico de revestimentos de concreto de cimento Portland aplicados a pavimentos permeáveis - Lamberti, Lucas Alves (2019)
The urbanization, associated with the population growth, is responsible for waterproofing surfaces, which increases inundation events frequency. To ease these problems, among other actions, come permeable pavements. This pavement is based on reduction of the surface runoff volume by allowing infiltration and storage of the water in its structure, and after that, the infiltration into the local soil. The objective of this work is to evaluate the structural and hydraulic performance of different permeable pavements to be built in the subtropical region of Brazil (Santa Maria-RS). We evaluated over the same structure, pervious concrete, pervious concrete pavers, concrete pavers and grass paver. Firstly, a laboratory investigation was carried out of the mechanical, hydraulic and durability characteristics of permeable concrete caused by differences in aggregate composition (unit mixture) in the mixture. Considering the best unit mixture, 1m² experimental modules were constructed to verify the effect of pore fouling over time, and then, parking lots to analyze the hydraulic efficiency of the permeable pavements under real conditions. It was concluded that the addition of 5% of sand and gravel combination between the 4.75/12.5mm and 9.5/25mm sieves in the permeable concrete provides a desirable gain of mechanical strength although it reduces the water percolation capacity. There was also a great heterogeneity in the value of the permeable concrete voids index implemented in the experiments when compared to the investigated in the laboratory, attributed to the workability of the mixture. Regarding the effect of sediment on the clogging, it was identified that those with higher grain size, such as sand, reduce the efficiency of permeable concrete more than materials with smaller grain size, such as clay, and that high pressure washing is able to recover floor efficiency. It was also observed that, among the analyzed coatings, the floors with permeable concrete, pervious concrete pavers and grass paver had similar hydrological performance.